Genetic resistance to parasitic diseases. African trypanosomiasis - Murray, M.; Trail, J.C.M.; Black, Samuel J. (Nebraska University, 1986)
Presents findings of a research carried out into the factors associated with genetic resistance to parasitic diseases in livestock Development projects in tsetse-infested areas of Africa. Indicates that trypanotolerant breeds of domestic livestock are capable of making a contribution towards alleviating Africa's food problem.